PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS - Titis Puspita Maharani; Tiffani Soffia Ningrum; Yuliana Anita sari; Fina Fakhriyah; Erik Aditia Ismaya (STKIP Subang, 2025)
This study aims to determine the effect of the Problem Based Learning model on the critical thinking skills of fourth grade students of SD Negeri 1 Payaman in the IPAS subject of cultural diversity. This study used a pre-experimental design with a one-group pretest-posttest approach and involved 13 students as subjects. The instrument used was 10 description questions based on critical thinking indicators according to Ennis. The data normality test was conducted with Shapiro-Wilk and showed that the data were normally distributed, with pretest and posttest significance values greater than 0.05. Furthermore, the paired sample t-test resulted in a Sig. value of 0.000 <0.05, so Ha was rejected and H0 was accepted, which means there is a significant difference between the pretest and posttest results. The average score of students increased from 60.85 to 83.23 with an N-Gain Score of 0.58 in the moderate category, the highest score was 89 and the lowest was 42. Thus, the Problem Based Learning model is proven to have a significant effect on improving students' critical thinking skills in IPAS learning.